Complementarity in action : a case study of the Thoams Kwoyelo case before the International Crimes Division of Uganda. - Killander, Magnus (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.